Marital Satisfaction and Sexual Satisfaction in Married Men in Tehran - Sayed Hadi Sayed Alitabar; Roya Hamidi; Saeid Ghanbari; Ali Zadeh Mohammadi; Mojtaba Habibi Asgarabad (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Premarital sex in big cities like Tehran, has increased significantly and could also have an impact on future relations people after marriage. The main objective of this study was to compare marital satisfaction and sexual satisfaction in married men with and without a history of premarital sex. Materials and Methods: This research was causal-comparative. The population of this study consists of all married men less than 45 years in Tehran. 144 married men in Tehran were selected by convenience sampling method. To collect the data, Kansas marital satisfaction and Enrich sexual satisfaction subscale were used. Independent sample t test were used for data analysis.   Results: The results showed that marital satisfaction in married men with a history of premarital sex other than with current wife with a mean (SD) 15.6 (4.1) is less than men with no history of 17.6 (3.5) (P<0.01). Sexual satisfaction in married men with a history of premarital sex other than with current wife with a mean (SD) 31.4 (6.9) is less than men with no history of 33.7 (5.4) (P<0.01). Marital and sexual satisfactions among married men with and without a history of sex with current partner were similar. Conclusion: This research suggests that married men with a premarital sexual history with other partners, have lower marital satisfaction and sexual satisfaction